Metamaterials based on the phase transition of VO2 - Liu, Hongwei (2019)
In this article, we present a comprehensive review on recent research progress in design and fabrication of active tunable metamaterials and devices based on phase transition of VO2. Firstly, we introduce mechanisms of the metal-to-insulator phase transition (MIPT) in VO2 investigated by ultrafast THz spectroscopies. By analyzing the THz spectra, the evolutions of MIPT in VO2 induced by different external excitations are described. The superiorities of using VO2 as building blocks to construct highly tunable metamaterials are discussed. Subsequently, the recently demonstrated metamaterial devices based on VO2 are reviewed. These metamaterials devices are summarized and described in the categories of working frequency. In each working frequency range, representative metamaterials based on VO2 with different architectures and functionalities are reviewed and the contributions of the MIPT of VO2 are emphasized. Finally, we conclude the recent reports and provide a prospect on the strategies of developing future tunable metamaterials based on VO2.